Analisis Tingkat Kepuasan Penumpang Bus Efisiensi Terhadap Kualitas Dan Kenyamanan Rute Purwokerto-Yogyakarta - Riyanto, Hanief Attalah Putra; Juanita, Juanita; Sari, Cremona Ayu Novita (Universitas Siliwangi, 2024)
AbstractIn general, one of the means of transportation that is still widely used by Indonesian people is the bus. The city of Purwokerto is the capital of Banyumas Regency, Central Java, which has a total area of 39.58 km². PO Efisiensi is a bus company originating from Kebumen, Central Java and is one of the intercity buses that is in great demand by the people of Purwokerto. Therefore, the author wants to analyze the level of service quality for passengers who use efficiency bus services in Purwokerto and what factors need to be improved to make passengers more comfortable. The method used in this research is Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) with data collection using the questionnaire method. This was carried out on 200 respondents and 30 questionnaires were tested on efficiency bus passengers, where the assessment used a Likert scale. The results of the analysis using the Importance Performance Analysis (IPA) method show that service performance on efficiency buses is in the Very Good/Very Satisfying category with a percentage of 98.94%. It can be said that the level of conformity to consumer expectations still needs to be improved. There are 3 attributes whose performance level of importance is still lacking, including Cleanliness. on the bus, the condition of the seat being comfortable to sit on, suitability of the route on the predetermined route. Public Transport Service Standards No.40 of 2015, 2020. The research results from the Customer Satisfaction Index (CSI) of 86.080% show that passenger satisfaction on the Purwokerto-Yogyakarta efficiency bus route is in the Very Good/Very Satisfying category regarding service performance on the Purwokerto-Yogyakarta efficiency bus route.Keywords: Importance Performance Analysis, Customer Satisfaction Index, Bus Passenger Expectations for Efficiency